The complete chloroplast genome sequence of Kadsura heteroclita - Wang, Qinghua (Mitochondrial DNA B Resour, 2020)
The first complete chloroplast genome (cpDNA) sequence of Kadsura heteroclita was determined from Illumina HiSeq pair-end sequencing data in this study. The cpDNA is 153,289 bp in length, contains a large single copy region (LSC) of 85,774 bp and a small single copy region (SSC) of 18,201 bp, which were separated by a pair of inverted repeats (IR) regions of 24,657 bp. The genome contains 129 genes, including 84 protein-coding genes, eight ribosomal RNA genes, and 37 transfer RNA genes. Further phylogenomic analysis showed that K. heteroclita and K. interior clustered in a clade in Schisandraceae family.